2010
DOI: 10.1016/j.apmr.2010.07.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wheelchair Tilt-in-Space and Recline Angles on Skin Perfusion Over the Ischial Tuberosity in People With Spinal Cord Injury

Abstract: Objective-To investigate the efficacy of wheelchair tilt-in-space and recline on enhancing skin perfusion over the ischial tuberosity in wheelchair users with spinal cord injury (SCI). Design-Repeated measures, intervention and outcomes measure design. Setting-A university research laboratory.Participants-11 wheelchair users with SCI (9 men, 2 women; mean age ± standard deviation, 37.7±14.2 years; body mass index 24.7±2.6 kg/m 2 ; and duration of injury 8.1±7.5 years).Interventions-6 protocols of various wheel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(125 citation statements)
references
References 42 publications
5
118
0
Order By: Relevance
“…Similar small movements of short duration were seen in a 2002 pilot study [36]. Although the effects of these movements on blood flow may be less significant [17,[43][44], they have the potential to change the internal deformation of tissue [11,45] and may provide important physiological benefits in terms of pressure ulcer prevention. Furthermore, small movements have the potential to help dissipate heat and reduce humidity [46].…”
Section: Ws Frequencymentioning
confidence: 63%
“…Similar small movements of short duration were seen in a 2002 pilot study [36]. Although the effects of these movements on blood flow may be less significant [17,[43][44], they have the potential to change the internal deformation of tissue [11,45] and may provide important physiological benefits in terms of pressure ulcer prevention. Furthermore, small movements have the potential to help dissipate heat and reduce humidity [46].…”
Section: Ws Frequencymentioning
confidence: 63%
“…5,18 However, this posture increases the pressure on the ischium and sacrum, and can cause ulcers. 6,14 In the present study, it was observed that individuals with SCI have a pelvic tilt in the sitting position, greater than individuals without such injury. An interesting fact observed is that the different cushions evaluated did not interfere with pelvic inclination, which suggests that the choice among these types of cushions does not have influence on the alignment between the ASIS, nor an effective action in the correct positioning of the sacrum.…”
Section: Discussionmentioning
confidence: 65%
“…An interesting fact observed is that the different cushions evaluated did not interfere with pelvic inclination, which suggests that the choice among these types of cushions does not have influence on the alignment between the ASIS, nor an effective action in the correct positioning of the sacrum. It is important, as a previous study 14 already demonstrated that the 1101 backrest inclination increases the pressure on the ischium and none of the types of cushions evaluated in the present study improved the pelvis tilt.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, recent studies have focused on evaluating the different effects of wheelchair tilt-in-space and recline angle on skin perfusion over the IT in wheelchair users with SCI by using laser doppler flowmetry [55]. Jan et al explained that to further understand the efficacy of wheelchair tilt-in-space and recline for decreasing PU risk, systemic research of the efficacy of various angles of wheelchair tilt-in-space and recline on decreasing skin and muscle perfusion ischemia is needed [55]. A transient increase in skin blood flow after ischemia is regulated by a protective mechanism called reactive hyperemia [48][49][50][56][57].…”
Section: Introductionmentioning
confidence: 99%